Before the wave: Exploring early perspectives on COVID-19 self-testing among African Americans in Eastern North Carolina - Tiarney D. Ritchwood; Kelsey Burton; Mysha Wynn (PLoS ONE, 2025)
Introduction In the first year of the COVID-19 pandemic, African Americans in rural communities faced disproportionate rates of hospitalizations and deaths. The emergence of the omicron variant further exacerbated these disparities, with African American adults approximately four times more likely to be hospitalized for COVID-19 compared to their White counterparts. To curb the transmission of the virus, public health professionals advocated COVID-19 mitigation strategies, including testing. However, barriers such as limited testing sites, long wait times, and privacy concerns hindered testing accessibility in rural areas. This study characterizes the early perceptions and acceptability of COVID-19 self-testing among African Americans in eastern North Carolina. Method We conducted semi-structured, small group discussions in November 2021 with participants representing three age groups (youth, adults, and older adults) from Eastern North Carolina. Data were analyzed thematically using deductive and inductive approaches. Results Findings indicate that, while self-testing was a novel concept for many participants, there was a high acceptability of COVID-19 self-testing. Barriers included low self-efficacy, concerns about test accuracy, and perceived costs. Participants emphasized the convenience and comfort of self-testing, recommending clear instructions, video demonstrations, and a toll-free number for help. Conclusions These insights offer valuable guidance for improving emergency testing strategies and protocols in response to future viral outbreaks and pandemic threats. Clear, user-friendly instructions and video demonstrations can enhance the accessibility of self-testing kits. Moreover, addressing concerns related to cost and test accuracy is crucial for widespread adoption. Public health campaigns should prioritize affordability, user-friendliness, and community-specific needs to foster resilience and equity in healthcare responses.